TRACING THE EMPLOYABILITY OF PHYSICAL EDUCATION GRADUATES IN NORTHERN PHILIPPINES - CARAG, EDUARDO ACEBO (International Journal of Psychosocial Rehabilitation, 2020)
This study entailed on tracing the employability of the Physical Education Graduates in Northern Philippines. It directed on the determination of the whereabouts of the graduates of College of Human Kinetics, Cagayan State University, Carig Campus. The demographic profile, educational background, employment profile and skills and competencies acquired were the factors of determination. This study adopted Slovin’s summed 178 respondents . This paper made used the CHED standard questionnaire for Graduate Tracer Survey. Based on the results of the study 60% of the graduates were employed in government and private entities. But only 28% of the graduates landed on professional teaching positions which is the main goal of the College, to produce competent teachers through a well-rounded program of Music, Arts, Physical Education and Health activities. It was suggested that there was a need for a management to revisit the curriculum enhancement to points out in the areas of faculty and instruction with special emphasis on licensure examination performance, admission and retention.